Relevance of embodied energy and carbon emissions on assessing cost effectiveness in building renovation – contribution from the analysis of case studies in six European countries - Almeida, Manuela Guedes de (2018)
The construction sector is facing increasingly strict energy efficiency regulations. Existing buildings have specific technical, functional and economic constraints, which, in fulfilling regulations, could lead to costly and complex renovation procedures and also lead to missed opportunities for improving their energy performance. In this article, the methodology for comparing cost-optimality in building renovations, developed in the International Energy Agency (IEA)?Energy in Buildings and Communities (EBC) Annex 56 project, is extended with a life cycle assessment by including embodied primary energy and carbon emissions in the calculations. The objective is to understand the relevance of embodied energy and carbon emissions in the evaluation of the cost-effectiveness of building renovation solutions towards nearly zero energy buildings, as well as the effect of the embodied values in the achievable carbon emissions and primary energy reductions expected in an energy renovation. Results from six case studies, representative of different regions in Europe, suggest that embodied values of energy and carbon emissions have a decreasing effect?ranging from 2 to 32%?on the potential reductions of energy and emissions that can be achieved with renovation measures in buildings. In addition, the consideration of the embodied energy and carbon emissions does not affect the ranking of the renovation packages.